2021
DOI: 10.1371/journal.pone.0252203
|View full text |Cite
|
Sign up to set email alerts
|

Tribological performance of organic molybdenum in the presence of organic friction modifier

Abstract: The tribological performance of organic molybdenum in the present of organic friction modifier was investigated in this study. Three types of organic friction modifiers were selected, which are Glycerol monooleate, Pentaerythritol and N,N-Dimethylhexadecylamine. The organic molybdenum are MoDTC, MoDDP and molybdenum amide. Friction coefficient and wear were studied in block-on-ring test rig with steel test specimens. Experimental results indicate the Pentaerythritol shows synergistic effect with MoDTC in wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[11][12][13][14][15] The most extensively studied compound is dialkyl dithiophosphate oxygen molybdenum (MoDDP) which can control wear, scuffing and friction. 16,17 To date, research studies have shown that the tribo-chemical decomposition of organic molybdenum and the decomposition product of MoS 2 are the critical factors to decrease the friction coefficient that can slide easily between the layers during the friction process. 16 It is generally accepted that the functionality of organo-molybdenum may be highly influenced by the presence of other functional additives in lubricants because the use of more than one modifier additive together may interact synergistically or antagonistically, 18 while the multiple additives in the system such as anti-wear (AW) additives, friction modifiers (FMs) and their interactions in the lubricant are critical to tribological performance.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] The most extensively studied compound is dialkyl dithiophosphate oxygen molybdenum (MoDDP) which can control wear, scuffing and friction. 16,17 To date, research studies have shown that the tribo-chemical decomposition of organic molybdenum and the decomposition product of MoS 2 are the critical factors to decrease the friction coefficient that can slide easily between the layers during the friction process. 16 It is generally accepted that the functionality of organo-molybdenum may be highly influenced by the presence of other functional additives in lubricants because the use of more than one modifier additive together may interact synergistically or antagonistically, 18 while the multiple additives in the system such as anti-wear (AW) additives, friction modifiers (FMs) and their interactions in the lubricant are critical to tribological performance.…”
Section: Introductionmentioning
confidence: 99%